2005
DOI: 10.1197/j.aem.2004.08.052
|View full text |Cite
|
Sign up to set email alerts
|

Patient Concerns about Medical Errors in Emergency Departments

Abstract: Objective: Despite large numbers of emergency encounters, little is known about how emergency department (ED) patients conceptualize their risk of medical errors. This study examines how safe ED patients feel from medical errors, which errors are of greatest concern, how concerns differ by patient and hospital characteristics, and the relationship between concerns and willingness to return for future care. Methods: Multiwave telephone interviews of 767 patients from 12 EDs were conducted. Patients were asked a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…In particular, in the emergency department (ED), up to 15% of patients are misdiagnosed (1). Medical malpractice litigation accounts for a high incidence of malpractice payments, and pediatricians are often the targets of such litigations (2).…”
mentioning
confidence: 99%
“…In particular, in the emergency department (ED), up to 15% of patients are misdiagnosed (1). Medical malpractice litigation accounts for a high incidence of malpractice payments, and pediatricians are often the targets of such litigations (2).…”
mentioning
confidence: 99%
“…In a multicentre series of interviews of patients discharged from the ED, the majority of ED patients indicated feeling relatively safe from medical errors, yet a significant percentage of patients expressed concern about a specific error during their ED encounter. 5 Only 1 previous study prospectively evaluated adverse events in patients discharged home from the ED. Two-week telephone follow-up of approximately 400 patients revealed a 6% incidence of adverse events, of which 63% led to an additional ED visit or hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that emergency department patients were attuned to environmental cues they perceived as linked to possible errors. 38 The staff culture required to ensure high levels of technical safety is also a culture that values empathy and patient centredness. Patient experience can be measured 39 and is an essential component of patient safety measurement.…”
Section: Patient Experiencementioning
confidence: 99%